Braneworld-f(R,T,G) - A.R.P. Moreira; Shi-Hai Dong (Nuclear Physics B, 2025)
This article explores how modifications to gravity influence the structure of the brane, with the goal of identifying the gravitational model that most closely reflects the one governing our physical universe. To achieve this, we consider a generalization of standard General Relativity. The stability of the model is evaluated through probabilistic measurements, revealing minimum points that represent the most probable and stable configurations of the brane for different values of the gravitational terms. Furthermore, the location of fermions on the brane is affected by gravitational variations, with the presence of resonance modes and the possibility of leakage of massive fermions into the bulk. Numerical analyses are presented, showing that the increase in the influence of gravitational terms increases the certainty of the location of massless fermions on the brane. All these results provide important insights for understanding the dynamics of the braneworld universe.